2021
DOI: 10.1097/mcg.0000000000001497
|View full text |Cite
|
Sign up to set email alerts
|

Digital Navigation Improves No-Show Rates and Bowel Preparation Quality for Patients Undergoing Colonoscopy

Abstract: Objectives: Because of high historical no-show rates and poor bowel preparation quality in our unit, we sought to evaluate whether text message navigation for patients scheduled for colonoscopy would reduce no-show rates and improve bowel preparation quality compared with usual care. Methods:We performed a randomized controlled quality improvement study from April to August 2019 in an urban academic endoscopy unit. All patients scheduled for colonoscopy were randomly assigned to a control group that received u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We found six trials (10.4%) with multiple intervention groups; these trials were included in more than one comparison 39 , 41 , 45 , 51 , 56 , 69 . The included studies were conducted in 13 countries: the United States (12 studies) 32 , 36 , 40 , 49 , 50 , 55 , 57 59 , 62 , 64 , 67 , China (10 studies) 16 , 35 , 37 , 46 , 47 , 52 , 63 , 69 , 71 , 72 , the Republic of Korea (9 studies) 31 , 38 , 39 , 41 , 44 , 45 , 51 , 53 , 54 , Spain (three studies) 29 , 48 , 60 , Hong Kong 42 , 43 , Germany 12 , 68 , and the Netherlands 17 , 66 (two studies each), and Australia 56 , Canada 65 , Denmark 34 , Lebanon 61 , Taiwan 70 , and the United Kingdom 30 (one study each). One study did not report the study setting 33 (Supplementary S8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found six trials (10.4%) with multiple intervention groups; these trials were included in more than one comparison 39 , 41 , 45 , 51 , 56 , 69 . The included studies were conducted in 13 countries: the United States (12 studies) 32 , 36 , 40 , 49 , 50 , 55 , 57 59 , 62 , 64 , 67 , China (10 studies) 16 , 35 , 37 , 46 , 47 , 52 , 63 , 69 , 71 , 72 , the Republic of Korea (9 studies) 31 , 38 , 39 , 41 , 44 , 45 , 51 , 53 , 54 , Spain (three studies) 29 , 48 , 60 , Hong Kong 42 , 43 , Germany 12 , 68 , and the Netherlands 17 , 66 (two studies each), and Australia 56 , Canada 65 , Denmark 34 , Lebanon 61 , Taiwan 70 , and the United Kingdom 30 (one study each). One study did not report the study setting 33 (Supplementary S8).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 47 included studies, 45 studies (95.7%) reported at least one of the primary outcomes 12 , 16 , 17 , 29 55 , 57 61 , 63 72 . The two most common outcomes were adequate bowel preparation rate and quality of bowel preparation score outcomes, which were investigated in 37 trials (78.7%) 12 , 16 , 17 , 29 , 30 , 32 , 35 44 , 46 50 , 52 – 54 , 57 , 59 61 , 63 70 , 72 and 34 trials (72.3%) 12 , 16 , 17 , 31 35 , 38 – 41 , 43 48 , 51 55 , 57 59 , 61 , 64 , 66 – 69 , 71 , 72 , respectively. (Supplementary S10) Various validated bowel preparation scales were used to evaluate the quality of bowel preparation in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported promising results of interventions to promote colonoscopy attendance using technology, primarily text messaging or short message services (SMS) [ 82 , 83 ]. Lam et al enrolled 2,225 patients scheduled for colonoscopy for any indication and randomized patients to receive a single SMS reminder 7–10 days prior to their appointment that included bowel preparation instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Solonowicz et al tested an intervention consisting of 20 text messages starting 14 days prior to the scheduled colonoscopy. Colonoscopy nonattendance rates were significantly lower in the SMS group compared to controls (8% vs. 14%; p < .0001) and rates of adequate bowel preparation for screening colonoscopies were higher in the SMS group (93% vs. 88%, p = .04) [ 83 ]. SMS-based communication shows promise for increasing attendance at screening colonoscopy appointments.…”
Section: Discussionmentioning
confidence: 99%
“…[103][104][105][106][107][108][109] Multicomponent patient navigation interventions (navigation combined with education and media) proved to be effective in promoting screening in both general and underserved populations, with higher screening uptakes. 103,105,107,109,110 Evidence from the studies suggests that culturally tailored or community-based programs with a focus on education, assistance with payments, transportation, and social networks with underserved populations (e.g., high-poverty rural counties in Texas, low-income Latina women, African F I G U R E 3 Summary of barriers and facilitators across the cancer continuum at the system, provider, and individual levels. EMR indicates electronic medical record.…”
Section: Early Detectionmentioning
confidence: 99%